Педагогическая характеристика совершенствования физических способностей юных курашистов - Нурышов, Д; Искендеров, Т (SCIENCE and SOCIETY, 2017)
The article deals with the pedagogical characteristics of the development of physical abilities of young fighters. There have been distinguished the meanings of such parameters as tiredness, physical loading and unloading, personal hygiene and others.
Keywords: kurash; quickness; power; technical eguipment; walk; running; cross